Analysis of tooth enamel after excessive bleaching: A study using scanning electron microscopy and energy dispersive X-ray spectroscopy - Souza, Rodrigo O.A.; Lombardo, Geraldo H.L. [UNESP]; Pereira, Sarina M.B. [UNESP]; Zamboni, Sandra C. [UNESP]; Valera, Márcia C. [UNESP]; Araújo, Maria A.M. [UNESP]; Özcan, Mutlu (My University, 2010)
This study assessed alterations on bovine enamel after excessive bleaching. Coronal portions of bovine teeth (n = 30) were sectioned and divided into three groups (n = 10 per group). The coronal parts were further cut incisocervically into two halves. While one half received no bleaching (control), the other half was subjected to either one (group 1), three (group 2), or five bleaching sessions (group 3) with 35% hydrogen peroxide. The enamel surfaces were then analyzed using scanning electron microscopy and energy dispersive x-ray spectroscopy (EDS). Excessive bleaching affected the surface morphology and chemistry of the bovine enamel. EDS analysis showed the highest decrease in calcium ion percentages in groups 2 and 3 when compared to their nonbleached halves. Oxygen and phosphorus percentages were comparable on both the control and bleached enamel, regardless of the number of bleaching sessions. Consecutive bleaching sessions with 35% hydrogen peroxide may lead to morphologic and specific elemental changes when performed in a short period of time. Calcium ion percentages may decrease when this bleaching agent is used for more than one session. © 2010 by Quintessence Publishing Co Inc.